A Molecular Landscape of Mouse Hippocampal Neuromodulation - Smith, Stephen J; von Zastrow, Mark (Frontiers in Neural Circuits, 2022)
Adaptive neuronal circuit function requires a continual adjustment of synaptic network parameters known as “neuromodulation”, a process prominently involving G protein-coupled receptors (GPCRs), signal transduction by heterotrimeric G proteins and regulation of ion channel gating downstream. Many of the basic molecular mechanisms of neuromodulation are now known, but the organization of neuromodulation at a network level has remained an enigma. Single-cell RNA sequencing now provides a bright light with which to illuminate this critical “dark matter” of neuroscience. Here we leverage recent advances in transcriptomics and neurotaxonomy to explore GPCR, G protein and ion channel gene expression across cell types and individual neurons in mouse hippocampus area CA1, with the goal of revealing broad outlines of that well-studied brain structure's neuromodulatory network architecture.